1998
DOI: 10.1128/jcm.36.11.3438-3440.1998
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nested PCR for Detection of Cryptococcus neoformans in Cerebrospinal Fluid

Abstract: We report the development of a nested-PCR-based assay for the detection of Cryptococcus neoformans in cerebrospinal fluid. The specificity and sensitivity of the test were assessed. The technique was then applied to 40 cerebrospinal fluid samples. We obtained positive reactions for all 21 clinical samples from patients who had been previously diagnosed as having cryptococcal meningitis by conventional techniques and negative reactions for all 19 negative controls. Nested PCR is here compared with other diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…A microtiter enzyme immunoassay (EIA) for the detection of Candida species in blood with a detection sensitivity of 2 cells/200 l of sample and a real-time fluorescent PCR-based assay for the detection of three Candida species in a single reaction tube with a detection sensitivity of 100 cells/ 200 l have previously been described (12,15). A nested PCR assay for the detection of C. neoformans in cerebrospinal fluid is reported to have a detection limit of 10 cells (29). Other researchers determined a detection level of 5 pg for A. fumigatus rDNA 18S gene amplicons in a microtiter plate EIA (10).…”
Section: Discussionmentioning
confidence: 99%
“…A microtiter enzyme immunoassay (EIA) for the detection of Candida species in blood with a detection sensitivity of 2 cells/200 l of sample and a real-time fluorescent PCR-based assay for the detection of three Candida species in a single reaction tube with a detection sensitivity of 100 cells/ 200 l have previously been described (12,15). A nested PCR assay for the detection of C. neoformans in cerebrospinal fluid is reported to have a detection limit of 10 cells (29). Other researchers determined a detection level of 5 pg for A. fumigatus rDNA 18S gene amplicons in a microtiter plate EIA (10).…”
Section: Discussionmentioning
confidence: 99%
“…There are five studies using PCR for the diagnosis of CNS cryptococcosis, three with evidence class III and two evidence class IV. Another study reported similar findings [157]. The third class III study compared culture, India ink test, and PCR in CSF of 56 patients with cryptococcal meningitis and 16 patients with meningitis of other origin [158].…”
Section: Cryptococcosis (Cryptococcus Neoformans/gattii)mentioning
confidence: 79%
“…Unlike other pathogenic fungi, pathogenic Trichosporon species rapidly disseminate to multiple organs. There are many reports of PCR-based diagnosis methods in aspergillosis (I, 12), candidiasis (2,11), and cryptococcosis (9,16), but as far as we know only one paper has reported a PCR-based method for disseminated trichosporonosis. Nagai et al (8) attempted to detect the DNA of Trichosporon species in the sera of patients histologically diagnosed with disseminated trichosporonosis using oligonucleotide primers designed from 28S rDNA sequences.…”
Section: Discussionmentioning
confidence: 99%